Model Asuhan - OD Sariningsih (Universitas Harapan Bangsa Purwokerto, 2020)
Child welfare is part of midwifery care. The phenomenon of sexual violence against children is increasingly occurring and is becoming almost global in various countries and continues to increase over time. Incidents of sexual violence that occurred during childhood (before age 15) one in five men (22.2%, 95% CI 20.5 to 23.9) and one in seven women (15.5%; 95% CI 14.1 to 17.0 ) reports of victims of physical or sexual violence during childhood. Perpetrators are family members (43%), fathers / stepfathers (29%) and teachers (15%), neighbors (20%), others (18%) and unknown strangers (15%). Child abuse in West Java reached 78 cases. The most reported violence occurred in Cirebon District (16 cases), Bogor City (11 cases), Bandung City (10 cases), and Bandung Regency (13 cases). The Early Prevention Midwifery Care Model is integrated into a strategy for preventing sexual violence in children 3-5 years by involving kindergarten teachers and parents of students. The study design used a quasi-experimental control group and intervention group through intervention, intervention and post intervention. The intervention population of 15 kindergarten children, parents and 2 teachers in TK SDK BPPK Bandung and a control group of 15 kindergarten children, parents and 2 teachers in TK BPPK Cimahi. The intervention group was given a model of integrated midwifery care through methods of preventing sexual violence against children. The control group was given an intervention about immunization. The analysis showed that there were significant differences before and after the intervention model of Midwifery Prevention Prevention Integrated Sexual Violence in Children 3-5 years was given, p = 0.004.